Defining the link between efflux pumps and biofilm formation. Issue 1 (31st January 2020) - Holden, Emma; Webber, Mark
Abstract : Biofilms are intrinsically important to our understanding of bacterial pathogens. The majority of bacterial life exists as part of a biofilm, as despite this, we have very little understanding of the genetic pathways that facilitate and drive biofilm formation. Work in our group has outlined a phenotypic link between efflux pump activity and biofilm formation, both of which have been implicated in decreased susceptibility to multiple antibiotics. Genetic or chemical inactivation of efflux results in a substantial decrease in biofilm formation. We have determined that this is due to transcriptional repression of one of the main components of the biofilm: the amyloid fibrous protein, curli. This relationship between efflux activity and biofilm formation has been identified in many Gram-negative and Gram-positive bacterial pathogens, but the regulatory network through which these phenotypes are linked is unknown. My PhD project aims to determine the pathway that links efflux pump activity and biofilm formation. I will investigate this using TraDIS, which is a large-scale transposon mutagenesis approach that will be used to determine all of the genes responsible for efflux activity and biofilm formation. My poster will present preliminary results from this genome-wide screen in E. coli . I will outline the further work to be undertaken, including repeating this experiment in Salmonella Typhimurium and formulating and testing hypotheses as to how efflux activity and biofilm formation are linked in both species. This will overall improve our understanding of important mechanisms of antimicrobial resistance in human pathogens.